Between Realism and Revolt Governing Cities in the Crisis of Neoliberal Globalism. - Davies, Jonathan (Bristol University Press, 2021)
Leading governance theorist Jonathan S. Davies develops a rich comparative analysis of austerity governance and resistance in eight cities, to establish a conjunctural perspective on the rolling crises of neoliberal globalism.